Effect of Co-Administration of Midazolam and Dexmedetomidine on Haemodynamics and Stress Response in Elderly Patients with Non-Small Cell Lung Cancer - Yanjun Zhao; Dongjiao An; Liang Bi (Journal of Investigative Surgery)
Objective This study aimed to evaluate the effect of co-administration of midazolam and dexmedetomidine on hemodynamics and stress response in elderly patients with non-small cell lung cancer (NSCLC).Methods In this prospective, randomized controlled trial, 154 elderly NSCLC patients scheduled for lobectomy in our oncology department from January 2019 to December 2021 were recruited. Patients were randomized 1:1 to receive either dexmedetomidine (control group) or dexmedetomidine plus midazolam (study group) for anesthesia during lobectomy via the random number table method, with 77 patients in each group. Perioperative indicators, hemodynamics, and stress reactions of the patients were recorded and compared between the two groups to investigate the efficacy of the two different anesthetic protocols.Results No significant differences were observed between the two groups in terms of operative time, anesthesia time, and intraoperative bleeding volume (p > 0.05). Preoperative pain, pain at anesthesia recovery, and pain levels 7 days postoperatively were also comparable between the two groups. In the study group, the awakening time was 15 ± 2 min significantly shorter compared to the control group (25 ± 3 min). Cooperation within the first hour was significantly faster by 8.5 ± 0.5 min compared to 6.0 ± 1.0 min in the control group (p < 0.05). The cost of materials used was significantly higher in the study group, with an average of 300 ± 25 USD, compared to 200 ± 20 USD in the control group (p < 0.05). Additionally, the two groups showed no significant difference in the need for experience and surveillance (p > 0.05). Significantly lower visual analog scale (VAS) scores were found one day after the surgery in patients given dexmedetomidine plus midazolam than those anesthetized administered with dexmedetomidine only, suggesting an enhanced pain mitigation effect after incorporating midazolam for anesthetic induction. Patients treated with dexmedetomidine plus midazolam presented with a more stable hemodynamic status than those treated with dexmedetomidine only, as evidenced by the significantly lower variability of mean arterial pressure (MAP), oxygen saturation (SpO2), and heart rate (HR). Co-administration of dexmedetomidine plus midazolam for lobectomy anesthesia resulted in significantly lower serum cortisol (Cor) and norepinephrine (NE) concentrations in patients at anesthesia recovery than dexmedetomidine alone. However, this difference was not observed one day postoperatively. There was no statistically significant difference in the incidence of adverse reactions between the two groups.Conclusion The combination of midazolam with dexmedetomidine anesthesia in lobectomy improves the intraoperative hemodynamic status of elderly patients with NSCLC and mitigates their stress response. However, further research is required to explore the underlying mechanisms.